X(x-3)(x+1)=

Simple and best practice solution for X(x-3)(x+1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X(x-3)(x+1)= equation:


Simplifying
X(x + -3)(x + 1) = 0

Reorder the terms:
X(-3 + x)(x + 1) = 0

Reorder the terms:
X(-3 + x)(1 + x) = 0

Multiply (-3 + x) * (1 + x)
X(-3(1 + x) + x(1 + x)) = 0
X((1 * -3 + x * -3) + x(1 + x)) = 0
X((-3 + -3x) + x(1 + x)) = 0
X(-3 + -3x + (1 * x + x * x)) = 0
X(-3 + -3x + (1x + x2)) = 0

Combine like terms: -3x + 1x = -2x
X(-3 + -2x + x2) = 0
(-3 * X + -2x * X + x2 * X) = 0
(-3X + -2xX + x2X) = 0

Solving
-3X + -2xX + x2X = 0

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Factor out the Greatest Common Factor (GCF), 'X'.
X(-3 + -2x + x2) = 0

Factor a trinomial.
X((-1 + -1x)(3 + -1x)) = 0

Subproblem 1

Set the factor 'X' equal to zero and attempt to solve: Simplifying X = 0 Solving X = 0 Move all terms containing X to the left, all other terms to the right. Simplifying X = 0

Subproblem 2

Set the factor '(-1 + -1x)' equal to zero and attempt to solve: Simplifying -1 + -1x = 0 Solving -1 + -1x = 0 Move all terms containing X to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -1x = 0 + 1 -1x = 0 + 1 Combine like terms: 0 + 1 = 1 -1x = 1 Add 'x' to each side of the equation. -1x + x = 1 + x Combine like terms: -1x + x = 0 0 = 1 + x Simplifying 0 = 1 + x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 3

Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing X to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Add 'x' to each side of the equation. -1x + x = -3 + x Combine like terms: -1x + x = 0 0 = -3 + x Simplifying 0 = -3 + x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Solution

X = {0}

See similar equations:

| A-6=77 | | 12x^4+8x^2-20=0 | | 245=x+166 | | -k+5(-3k+3)=15-4K | | P^3-4p^2=O | | w+2=98 | | sen4x=1/2 | | 5+14a=9a-2 | | 15+14p=2 | | 3(-4)=9 | | j-47=29 | | 2x+1+2x=96 | | (8)/(3X^2) | | -3x^2+24x=17 | | 92=x+20 | | y+2.7=18.3 | | 120n=1320 | | 39-3x=7(x+2)-5 | | A-15x=0 | | y=-0.5*2 | | 6a=126 | | 1.25=2x | | X/2=18/x | | 3x-34=2(x-18) | | 2.42 = p2 | | 3(3x-3)=21 | | (X+3)-2X=35+X | | 16(x+2)-4x=4(3x+2)-9 | | 8x+66=3x+31 | | x+46=5x+10 | | 89=1x+100 | | 24-9=5x |

Equations solver categories